Menghidupkan Budaya Literasi di Lingkungan Sekolah SDS Al-Amien Pamekasan - Devie Reztia Anjarani; Fetty Nuritasari; Anisa Fajriana Oktasari; Yuliarsih Yuliarsih; Rohmah Indahwati (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The Community Service (PkM) activity carried out by the Madura University PKM team with the theme "Changing literacy culture into a learning environment at SDS Al-Amien Pamekasan Pamekasan" was carried out by the Madura University community service team involving teachers to learn more about the dynamics and growth of reading gardens to then further encourage the reading tradition or the reading culture of the community. society to develop as students in modern times in the future.  The activity which lasted for three days succeeded in providing soft skills and motivation to teachers and students of SDS Al-Amien Pamekasan. The proposal for this training is the need for all parties to participate in supporting the program so that the younger generation in particular and the community have a literacy culture and become learners in all the developments of life to grow bigger. In addition to deep motivation for the younger generation and society, it is also important for students to be able to fulfill their potential by developing a reading culture, especially how to read and deliver literary works effectively. This positive activity became a real work among students who were born from a love of reading